Performance of the medical priority dispatch system in correctly classifying out-of-hospital cardiac arrests as appropriate for resuscitation. (December 2022) - Yap, Justin; Helmer, Jennie; Gessaroli, Marc; Hutton, Jacob; Khan, Laiba; Scheuermeyer, Frank; Wall, Nechelle; Bolster, Jennifer; Van Diepen, Sean; Puyat, Joseph; Asamoah-Boaheng, Michael; Straight, Ron; et al.
Abstract: Background: Emergency dispatch centres receive emergency calls and assign resources. Out-of-hospital cardiac arrests (OHCA) can be classified as appropriate (requiring emergent response) or inappropriate (requiring non-emergent response) for resuscitation. We sought to determine system accuracy in emergency medical services (EMS) OHCA response allocation. Methods: We analyzed EMS-assessed non-traumatic OHCA records from the British Columbia (BC) Cardiac Arrest registry (January 1, 2019-June 1, 2021), excluding EMS-witnessed cases. In BC the "Medical Priority Dispatch System" is used. We classified EMS dispatch as "emergent" or "non-emergent" and compared to the gold standard of whether EMS personnel decided treatment was appropriate upon scene arrival. We calculated sensitivity, specificity, and positive and negative predictive values (PPV, NPV), with 95% CI's. Results: Of 15, 371 non-traumatic OHCAs, the median age was 65 (inter quartile range 51–78), and 4834 (31%) were women; 7152 (47%) were EMS-treated, of whom 651 (9.1%) survived). Among EMS-treated cases 6923/7152 had an emergent response (sensitivity = 97%, 95% CI 96–97) and among EMS-untreated cases 3951/8219 had a non-emergent response (specificity = 48%, 95% CI, 47 to 49). Among cases with emergent dispatch, 6923/11191 were EMS-treated (PPV = 62%, 95% CI 61–62), and among those with non-emergent dispatch, 3951/4180 were EMS-untreated (NPV = 95%, 95% CI 94–95); 229/4180 (5.5%) with a non-emergent dispatch were treated by EMS. Conclusion: The dispatch system in BC has a high sensitivity and moderate specificity in sending the appropriate responses for OHCAs deemed appropriate for treatment by paramedics. Future research may address strategies to increase system specificity, and decrease the incidence of non-emergent dispatch to EMS-treated cases.